Islam and Culture (Ritual and Intuition) - Darwis, Muhajir; Rahmawati, Suci; Ningrum, Evi Wulan; Afrawasih, Nisa; Nuradha, Nuradha; Agustian, Raihan; Syahrul, Syahrul (CV. Rayyan Dwi Bharata, 2024)
This article aims to discuss the complex relationship between Islam, culture, rituals, and intuition. The research is based on a literatue review. In the context of Islam, rituals and intuition play crucial roles in shaping the religious experience and cultural expression of Muslim communities. Islamic rituals are not only religious acts but also manifestations of traditional values and collective identity. On the other hand, intuitions allows individuals to approach religious truths personally, transcending the limits of rationality. In this article, we explore how rituals and intuition complement and enrich each other in the context of Islam, as well as the implications of this relationship for cultural and Muslim identity. Through this analysis, we hope to provide deeper insights into the religious and cultural life of Muslims and enrich intercultural relationships in society.